Opinion 2427: Lepisma Linnaeus, 1758 (Insecta, Zygentoma, Lepismatidae): Direction 71 (1957) reversed - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has used its plenary power to rescind Direction 71, which was issued in 1957 and which deemed deeming Lepisma Linnaeus, 1758 to be of feminine gender and all generic names derived from it (i.e. those ending in -lepisma) are now ruled to be of neuter gender.
Keywords: Nomenclature; taxonomy; gender; Insecta; Zygentoma; Thysanura; Lepismatidae; Afrolepisma; Anisolepisma; Asiolepisma; Burmalepisma; Cretalepisma; Ctenolepisma; Gopislepisma; Hemilepisma; Heterolepisma; Hyperlepisma; Lepisma; Leucolepisma; Mirolepisma; Nebkhalepisma; Neoasterolepisma; Ornatilepisma; Panlepisma; Protolepisma; Tricholepisma; Psammolepisma; Sabulepisma; Sceletolepisma; Swalepisma; Xenolepisma; saccharina; longicaudata; silverfish